HotPLUZ: A BGP-aware Green Traffic Engineering Approach - Ruiz-Rivera, A.; Chin, K.; Raad, R.; Soh, Sie Teng (IEEE, 2014)
Green networking techniques aim to shut down the least utilized links and/or routers during off-peaks hours. In this paper, we show that such techniques negatively impact the operation of the Border Gateway Protocol (BGP). We quantify the impacts of two representative green approaches: (i) GAES, a green technique that modifies link weights, and (ii) ESOL, a green technique that does not involve link weights adjustments. Experiments over the Abilene, AT&T, GEANT and SURFnet topologies show that when using GAES, routing changes and the proportion of rerouted traffic, both of which affect BGP, are in the order of 108% and 141% greater than ESOL. Therefore, we propose Hot Potato Low UtiliZation (HotPLUZ), a greenapproach that takes hot-potato routing into account. HotPLUZ reroutes traffic from lowly utilized links and aggregate said traffic onto highly utilized links, whilst minimizing any changes to the corresponding egress router of a given destination. In addition, HotPLUZ considers link utilization in order to avoid packet loss and high latencies. Our experimental results indicate an overall saving of up to 21% under low network load.